Production of humic substances and available nutrient status in soil profile under multipurpose tree species of arid and semiarid region - KAUSHIK, SUBHANU; DEVRAJ, DEVRAJ; KUMAR, RAVI; ANTIL, R S (The Indian Journal of Agricultural Sciences, 2015)
To study the effect of different tree species on organic carbon, production of humic substances and nutrient status in soil profile under different tree species, five blocks of different tree plantations, viz. Prosopis cineraria, Dalbergia sissoo, Acacia nilotica, Eucalyptus tereticornis and Tamarix aphylla were selected. Seven soil samples depth wise up to 150 cm from each soil profile including six one without plantation (control) was collected and analyzed for organic carbon, humic acid, fulvic acid and available nutrient status in soil. The organic carbon content decreased with increase in soil depth and highest organic carbon was found in surface layer of Dalbergia sissoo in comparison to other tree species and control. Similarly humic acid and fulvic carbon decreased with increase in soil depth and maximum humic acid was found under Dalbergia sissoo and in fulvic acid, it was highest under Acacia nilotica and minimum in control in both the cases. The available nutrients were decreased with increase in depth higher amount of nutrients were found under tree species as compared to control. It may be concluded that tree litter falling from Acacia nilotica, Dalbergia sissoo and Prosopis cineraria was stabilized enough and improved the availability of nutrients in soil. The intercrop may be taken up successfully between the trees of these plantations. In case of Eucalyptus tereticornis and Tamarix aphylla, more time is needed for stabilization and decomposition of litter for their better management and high returns.